STRATEGI KOMUNIKASI PEMASARAN DOMPET DHUAFA DALAM MENINGKATKAN KEPERCAYAAN MUZAKKI - Tarsani Tarsani (Universitas Bunda Mulia, 2016)
This research study of marketing communications strategy practiced by Dompet Dhuafa in improvingmuzakki. And chose this case for marketing cmmunicatios strategy is vital to nonprofit /socialinstitution especially institution of Amil and Zakat to survive, more advanced and believed the publicso they want of charitable disbursing funds infak and shadaqah through LAZ concerned. DompetDhuafa as an institution of amil zakat national level, which have been confirmed by the decree of theminister of religious affairs 439 dated the 8 october 2001, having various program sustainable anduseful for the society. This institution is one of the largest LAZ in Indonesia althogh many similarspiringing social institution. Among the key to the success of the Dompet Dhuafa people is major lazand trusted of marketing communications strategy creative innovative and effective. Methods used inthis researh is qualitative with the kind of research laz Dompet Dhuafa case study in Jakarta theparadigm is konstruktivis paradigm that is used. Researchers found that srategy of marketingcommunications done LAZ Dompet Dhuafa, consisting of two models is collecting fund and donorservices strategy. Collecting fund activity performed by some means;fundrising, among other methodsmedia campaign make newa,advertising,hold event in central boisterousness picklock ambassador andpublic figure as rogram. While donor services comprising;access brzakat,eas a system ofmembership,wisata zakat and publication report. Marketing communications strategy the increasetrust so far succesfully muzakki against Laz Dompet Dhuafa so that these institutions to grow fromdonor number and multiplyKeywords : Strategy, Marketing Communication, Dompet Dhuafa, Muzakki